François Queyrel. La Sculpture hellénistique I: forms, themes et fonctions. - Barringer, Judith (Journal of Greek Archaeology, 2018)
Queyrel’s latest tome is a big, richly-illustrated one: the first of two dedicated to Hellenistic sculpture projected for Picard’s Les Manuels d’art et d’archéologie antiques. The series, which already includes volumes on the Bronze Age, on Classical Greek sculpture (by †Claude Rolley, one of the persons to whom this volume is dedicated), and on Greek architecture, has become an essential tool for scholars, teachers, and students.